Nerve-associated neural crest: peripheral glial cells generate multiple fates in the body. (August 2017) - Petersen, Julian; Adameyko, Igor
Highlights: In the article by Petersen and Adameyko, the story of Schwann cell precursor's (SCPs) multipotency develops step by step informing the reader about the key role of SCPs in producing various cell types in a vertebrate embryo. Recently, nerve-associated SCPs turned out to be a multipotent neural crest-derived cell type. SCPs generate melanocytes, parasympathetic and enteric neurons, Schwann cells and mesenchymal cells. Evolutionary, SCPs may represent the most ancient version of neural crest dispersal throughout the body. Abstract : Recent studies demonstrated that neural crest-derived Schwann cell precursors (SCPs) dwelling in the nerves are multipotent and can be recruited in the local tissue to provide building blocks of neural crest-derived nature. The variety of fates produced by SCPs is widening with every year and currently includes melanocytes/melanophores, parasympathetic and enteric neurons, endoneural fibroblast, mesenchymal stem cells and, of course, mature Schwann cells of different subtypes. However, it is still unclear if SCPs are, in fact, nerve-dwelling population of the neural crest or they are rather a different, more specialized, cell type. This review outlines the field and focuses on the capacity of nerve-associated glial progenitors to contribute to the development and regeneration of numerous tissues in various groups of vertebrates.